Final results of the US humanitarian device exemption study of the low-profile visualized intraluminal support (LVIS) device. (21st September 2015) - Fiorella, David; Arthur, Adam; Boulos, Alan; Diaz, Orlando; Jabbour, Pascal; Pride, Lee; Turk, Aquilla S; Woo, Henry H; Derdeyn, Colin; Millar, John; Clifton, Andrew
Abstract : Introduction: The low-profile visualized intraluminal support (LVIS) device is a new, braided, intracranial microstent designed for stent-assisted coiling. Objective: To present the results of a single-arm, prospective, multicenter trial of the LVIS for treatment of wide-necked intracranial aneurysms. Methods: 31 patients with unruptured, wide-necked (neck ≥4 mm or dome:neck ratio ≤2) intracranial aneurysms were treated with the LVIS device and bare platinum coils at six US centers (investigational device exemption G110014). Clinical follow-up was conducted at 30 days and 6 months. Angiographic follow-up was performed at 6 months. The primary safety endpoint was any major stroke or death within 30 days or major ipsilateral stroke or neurological death within 6 months. 'Probable benefit' was defined as ≥90% angiographic occlusion at 6 months. An independent core laboratory adjudicated the angiographic results. An independent clinical events committee adjudicated the clinical endpoints. Results: Average aneurysm size was 7.2 mm (SD 3.8) and average neck width was 4.6 mm (SD 1.8). 68% of patients had a dome:neck ratio ≤2. LVIS placement was technically successful in 29/31 patients (93.5%). No primary safety endpoints occurred during the study (0%). No patient had a higher modified Rankin Score at 6 months than at baseline. 26/28 (92.9%) treated aneurysms with 6-month angiographic follow-up demonstrated ≥90% angiographic occlusion. 21/28 (75%) were completely occluded at follow-up. Conclusions: The LVIS device facilitated the coil embolization of wide-necked intracranial aneurysms with high rates of technical success, an excellent safety profile, and very high rates of complete and near-complete occlusion at follow-up. Trial registration number: NCT01541254.